Knowledge, practices and gender discrepancies of migrant labours concerning malaria in Bhubaneswar, Odisha, India - Tripathy, Asima; Mohanty, Aswini Kumar; Kar, Shantanu Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Bhubaneswar, the capital of Odisha is an up-coming city since 1960s. The capital is undergoing various developmental activities and rapid industrialization. This is leading to migration of labours from various districts of Odisha including malaria endemic districts. The records available in central malaria laboratory, Bhubaneswar revealed high malaria incidence (ranged from 5% to 11% during last five years). Methods: The study was undertaken in Bhubaneswar, Odisha, India, on migrant laboures (300 samples) through a pre-structured schedule. Results: The study revealed the migrated respondents were from malaria endemic districts of Odisha. The malaria endemicity of the districts ranged from 2.2-9.8. It was also found that only 6% of the migrants were from low endemic areas i.e. SPR<5 But another 94% of the migrants were from high endemic areas i.e. SPR>5. Study of the awareness of the respondents showed 31% males and 9% females knew mosquito bite as a cause of malaria. Rapid Diagnostic Test showed twenty seven numbers of respondents tested positive for malaria (24 positive for PF and 3 positive for PV), out of them 6 were males and 21 were females. The study of their sleeping habits and personal protection methods showed that 32% respondents slept outdoor and 73% did not use anything as protection against mosquito bite. The study regarding knowledge of malaria signs and symptoms among respondents showed that the most commonly recognized signs and symptoms of malaria were headache (23%). Vector incrimination study showed that per man hour density of an. stephensi is 5.7. Conclusions: Thus presence of efficient malaria vectors and inadequate knowledge in the migrant labour community and emphatically among female migrant labours regarding cause, symptoms, prevention, control measures and risks associated with malaria is the major reason of malaria transmission.